Anti-bacteria and toxicity potential of a rare Actinobacterium Pseudonocardia sp. SM1A, isolated from Mangrove Park, West Kalimantan, Indonesia - RISA NOFIANI; RIZKY RIZKY; RIDHO BRILIANTORO; PUJI ARDININGSIH (Society for Indonesian Biodiversity, 2022)
Abstract. Nofiani R, Rizky, Briliantoro R, Ardiningsih P. 2021. Anti-bacteria and toxicity potential of a rare Actinobacterium Pseudonocardia sp. SM1A, isolated from Mangrove Park, West Kalimantan, Indonesia. Biodiversitas 23: 453-458. This study aimed to identify and evaluate antibacterial and toxicity activities of a rare Actinobacterium isolated from mangrove mud, Mempawah District, West Kalimantan. The mangrove mud sample was inoculated on ISP4 agar dissolved with seawater enriched meropenem (75µg/mL) and nystatin (100 µg/mL) using pour plate procedure and incubated at room temperature until the appearance powdery colony. One of the 2 powdery colonies successfully isolated was SM1A. SM1A was morphologically and biochemically identified to determine its genus and tested antibacterial activities using the cross streak method. SM1A also was cultivated and shaken at room temperature. After 10 days, the culture was extracted using ethyl acetate and then the extract was tested antibacterial activities using a well diffusion method and toxicity using brine shrimp lethality test (BSLT). SM1A was identified as Pseudonocardia sp., then was called Pseudonocardia sp. SM1A. Pseudonocardia sp. SM1A tested anti-bacteria using the cross streak method showed active against Staphylococcus aureus, Salmonella typhi, Escherichia coli, Pseudomonas aeruginosa, Vibrio cholera, and Streptococcus mutants for the ISP4 agar medium and S. typhi, S. mutants, and V. cholera for the ISP1. Pseudonocardia sp. SM1A extract prepared from ISP1 broth medium was active against S. typhi, E. coli, V. cholera, and Streptococcus mutants. In addition, Pseudonocardia sp. SM1A extract cultivated on ISP1 broth medium showed LC50=11.2570 µg/mL based on the BSLT and categorized as moderately toxic level. Pseudonocardia sp. SM1A contained secondary metabolites having high potential as lead compounds for drug discovery.